DEVELOPING OF GLOBALIZATION AND MASS MEDIA IN THE WORLD, ESPECIALLY USA - Ahmedov Azimjon Ilhomovich the teacher of Andijan State Institute of Foreign Languages; Oribova Matluba, Shukurova Xolisxon Sodiqova Maxliyo the student of Andijan State Institute of Foreign Languages, 312-group – English language; literature (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
The Global Media Defence Fund supports not-for-profit civil society organizations working on the ground to implement innovative programming for enhancing media protection and improving the access of journalists to specialized and gender-sensitive legal assistance.